2020
DOI: 10.1177/1363461520949672
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology among apprentice traditional health practitioners: A quantitative study from rural KwaZulu-Natal, South Africa

Abstract: Sociocultural context seems to influence the epidemiology, phenotype, treatment, and course of psychosis. However, data from low- and middle-income countries is sparse. This research is part of a multidisciplinary and multimethod study on possible mental disturbances, including hallucinations, among (apprentice) traditional health practitioners (THPs) who have experienced the “ancestral calling to become a THP” in rural KwaZulu-Natal, South Africa. The aim of the current article is to examine whether the calli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…In a subsequent epidemiological study, we have examined the manifestations of the ancestral calling among a group of apprentice THPs from a psychiatric diagnostic perspective. (Van der Zeijst et al, 2021).…”
Section: Conceptualization Of the Ancestral Callingmentioning
confidence: 99%
“…In a subsequent epidemiological study, we have examined the manifestations of the ancestral calling among a group of apprentice THPs from a psychiatric diagnostic perspective. (Van der Zeijst et al, 2021).…”
Section: Conceptualization Of the Ancestral Callingmentioning
confidence: 99%
“…Although current internationally adopted classifications of mental disorders are used across cultures and contexts globally (Gureje et al, 2019;Gureje, Lewis-Ferna´ndez, et al, 2020), there is an acknowledgement that the definitions of the disorders are mostly based on norms derived from Western Europe and North America (Lucas & Barrett, 1995). An exploration of this situation is provided in this issue by van der Zeijst, Veling, Makhathini, Mtshemla, et al (2021), who report findings from a series of in-depth interviews and a cross-sectional descriptive study of trainee traditional healers. They found that some unusual experiences that would otherwise meet current definitions of psychopathological phenomena were either regarded as normal in the emic view of rural KwaZulu-Natal, South Africa, or even esteemed as evidence of extraordinary ability to communicate with ancestral spirits (Lee, 1969).…”
Section: Cultural Understanding Of Mental Illnessmentioning
confidence: 99%
“…In two prior studies, we emically ( 13 ) and etically ( 14 ) examined unusual perceptual experiences and other mental disturbances among a specific group of individuals who visited THPs in Vulindlela, a rural area in KwaZulu-Natal, South Africa. Our first, ethnographic, study ( 13 ) included interviews with 20 THPs, apprentice THPs, patients and relatives who were visiting THPs, patients with a psychotic diagnosis who were visiting a formal health clinic, and biomedical health practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…They had transformed into well-functioning and respected members of the society with a defined work, role and social status as THPs, and their hallucinatory experiences remained an instrumental part of their healing profession. In our second study ( 14 ), we assessed 48 apprentice THPs who were undergoing ukuthwasa – individuals who are called amathwasa – to see whether and how their calling-related mental disturbances could be interpreted from a Western, psychiatric perspective. Our results showed that psychotic and mood-related experiences, symptoms and disorders were common in this group, confirming suggestions from other studies ( 19 – 23 ) and our own ethnographic study ( 13 ) that there is a relationship between the cultural construct of ancestral calling to become a THP and what Western psychiatry would characterize within the context of psychosis.…”
Section: Introductionmentioning
confidence: 99%